To Compare the Diagnostic Sensitivity of ZN (Ziehl-Neelsen) Staining, CBNAAT (Cartridge Based Nucleic Acid Amplification Test) and Mycobacterium Culture of BAL (Bronchoalveolar Lavage) Fluid among Sputum Smear Negative or Non- Sputum Producing Patients wi - Vipin Deo Tiwari; Mazher Maqusood; G. Ramakrishna; Rajul Rastogi (Asian Journal of Medical Research, 2020)
Background: Compare the diagnostic sensitivity of ZN staining and CBNAAT using Mycobacterium Culture as a gold standard in BAL fluid among sputum smear negative or non- sputum producing patients with suspected pulmonary tuberculosis.Subjects and Methods:Our prospective observational study was conducted on 76 patients either attending Outpatient Department or being admitted in the department of Pulmonary Medicine, Teerthanker Mahaveer Medical College & Research Centre, Moradabad (UP). BAL sample obtained using a flexible fibre-optic bronchoscope from sputum smear negative or non- sputum producing patients with suspected pulmonary tuberculosis. Sample was divided into three parts and send the BAL fluid for CBNAAT, ZN staining, and Mycobacterium liquid culture and compare the diagnostic sensitivity of ZN staining and CBNAAT using Mycobacterium Culture as a gold standard in BAL fluid.Results: Our study was carried out on 76 patients, ZN staining detected positive and negative in BAL samples among 17.1% and 82.9% respectively. CBNAAT detected positive and negative in BAL samples among 68.72% and 31.6% respectively. Among the positive detected specimens, rifampicin resistance and sensitive were found among 4 (5.56%) and 48 (63.16%) specimens respectively.MTB detected positive and negative in BAL samples among 51.3% and 48.7% of the subjects respectively. The gold standard BAL-MTB liquid culture was used to test the efficacy of ZN staining to detect the BAL specimen. Sensitivity, specificity, PPV, NPV, and Accuracy of ZN in the detection of BAL specimen were 23.08%, 89.19%, 69.23%, 52.38%, and 55.26% respectively. Sensitivity, specificity, PPV, NPV and Accuracy of CBNAAT in detection of BAL specimen were 92.31%, 66.76%, 79.23%, 87.50% and 75% respectively.Conclusion: Gene Xpert MTB/RIF assay is efficient and reliable technique for the smear negative cases. Its simplicity, sensitivity, speed and automation, make this technique a very attractive tool for diagnosis of pulmonary tuberculosis in smear negative cases of TB suspects. Meanwhile it has an added advantage of detection of multi-drug resistant cases.